2013
DOI: 10.1002/jbmr.2067
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral Size, Bone Density, and Strength in Men and Women Matched for Age and Areal Spine BMD

Abstract: To explore the possible mechanisms underlying sex-specific differences in skeletal fragility that may be obscured by two-dimensional areal bone mineral density (aBMD) measures, we compared quantitative computed tomography (QCT)-based vertebral bone measures among pairs of men and women from the Framingham Heart Study Multidetector Computed Tomography Study who were matched for age and spine aBMD. Measurements included vertebral body cross-sectional area (CSA, cm2), trabecular volumetric BMD (Tb.vBMD, g/cm3), i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 45 publications
0
36
0
Order By: Relevance
“…Structural rigidity depends on bone size and elastic modulus, (16) which was estimated from a previously published relationship: Elastic modulus = −34.7 + 3230 × Int.vBMD (34) …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural rigidity depends on bone size and elastic modulus, (16) which was estimated from a previously published relationship: Elastic modulus = −34.7 + 3230 × Int.vBMD (34) …”
Section: Methodsmentioning
confidence: 99%
“…According to previously published methods, (16,36,37) in the biomechanical model, the body was divided into sections, and each section’s length, weight, and center of mass position were estimated, and the muscle forces required to maintain static equilibrium during each activity were calculated. For each activity, the applied load to the L4 vertebral body was determined by totaling all forces (from body weight and muscle loading) in the axial direction of L4.…”
Section: Methodsmentioning
confidence: 99%
“…The size and shape of the femur (hip geometry) is critical to the mechanical strength of the hip and its resistance to fracture under various loading conditions. For example, at the same volumetric density, male bones are stronger because they are larger (79). Hip geometry can be estimated from 2-dimensional DXA images.…”
Section: Rationalementioning
confidence: 99%
“…It often leads to non-traumatic vertebral fractures with consequent morbidity and has negative effects on the quality of life12. A systematic review suggested that small vertebral size is an independent risk factor for vertebral fractures3.…”
mentioning
confidence: 99%
“…Causing changes in these factors, age affects vertebral strength to a large extent8910. Men are known to have larger vertebral cross-sectional area (CSA), both absolute and relative to body size, as well as greater compressive strength than women111. Regardless of gender, bone mass reaches its maximum value between the ages of 20 and 30 years, decreasing thereafter10.…”
mentioning
confidence: 99%